Clinical Evaluation of Bridelia scandens Willd. (Banda) Leaf Powder and Leaf Oil in the Management of Amavata (Rheumatoid Arthritis): An Open-Label Comparative Clinical Study - Bhatta, Raghurama; Rao S, Ravi; B, Rajani; M, Shubha (Journal of Neonatal Surgery, 2025)
Background: Amavata is a chronic inflammatory disorder described in Ayurvedic classics, considered analogous to rheumatoid arthritis (RA). Contemporary treatment options provide symptomatic relief but are often associated with adverse effects and incomplete remission. Bridelia scandens Willd. (Banda), an ethnomedicinal climber traditionally used in Dakshina Kannada District, Karnataka, has been employed for generations in the management of painful inflammatory joint disorders. Objectives: To evaluate the clinical efficacy and safety of Bridelia scandens leaf powder alone and in combination with Bridelia scandens leaf oil in patients with Amavata. Materials and methods: An open-label comparative clinical study was conducted. Twenty patients with Amavata were enrolled; fifteen completed the study. Group I (n=8) received oral Bridelia scandens leaf powder (6 g/day). Group II (n=7) received oral leaf powder plus topical leaf oil for 30 days. Assessment was based on graded scores for Sandhishoola, Sandhishotha, Sandhigraha, and Sparshasahatva. Results: Group I showed statistically significant improvement in Sandhishoola (56.28%), Sandhishotha (53.76%), Sandhigraha (49.19%), and Sparshasahatva (48.95%) (P<0.001). Group II demonstrated greater improvement: Sandhishoola (60.83%), Sandhigraha (62.50%), Sparshasahatva (58.77%), and Sandhishotha (53.55%) (P<0.001). Combined therapy produced 32.32% higher efficacy compared to oral therapy alone (P<0.05). Conclusions: Bridelia scandens demonstrated significant anti-inflammatory and analgesic effects in Amavata. Combined oral and topical administration was superior to oral therapy alone, validating the traditional folklore use of the plant in arthritic disorders